Comportamiento del consumidor de purificadores de agua para el hogar en la ciudad de Machala - Ramirez Melendrez, Dario Javier (2015)
Overall this study is based on collecting and analyzing consumer data provided in the city of Machala preferences of buyers and water purifiers explored. Existing diseases through the years caused by misuse of drinking water led the study and creation of a proposal based on marketing strategies momentum in sectors where data were provided. The high degree of discomfort in the health of people is reduced through scientific studies and technological advances producing tools that over the years is constantly evolving, it concludes with the design and creation of a small business dedicated to marketing purifiers water, offering quality, service, cost effective products that provide healthier quality of life in families of the city. The result of this project gave no notion that people are guided to make purchases on commercial grounds as inexpensive product available to the pockets of families. Seeks to satisfy themselves of changing consumption that provides the environment needs to complete the findings that we have considered going to help us in reducing barriers that nations have to have quality processed water of cities that cities that do not have priority the welfare of the people, possible with low investment or Budget